Online Dispute Resolution Scheme over Consumer’s Loss as Consumer Protection in Cross-Border E-Commerce Transaction - Zahwa Maulidina Afwija (POLICY, LAW, NOTARY AND REGULATORY ISSUES, 2025)
Consumers are facing greater risk of loss in cross-border e-commerce due to lack of thorough goods inspection, uncertainties in jurisdiction, and high costs of legal actions. However, current methods for resolving disputes are not effectively handling these issues. This research explores the urgency of implementing Online Dispute Resolution (ODR) to protect consumers in cross-border e-commerce transactions, focusing on Indonesia and the United Kingdom. As cross-border digital trade increases, consumers are increasingly vulnerable to losses due to limited inspection of goods, jurisdictional uncertainties, and the high cost of traditional litigation. Employing a normative legal research method with a comparative and conceptual approach, this study examines the regulatory framework governing e-commerce and dispute resolution in both jurisdictions. The findings reveal that although Indonesia’s legal system acknowledges alternative dispute resolution through instruments such as UUPK, UU ITE, and PP PMSE, it lacks detailed procedural regulations for effective ODR implementation. In contrast, the United Kingdom has established a comprehensive ODR system regulated by EU Regulations and Directives, offering structured online platforms for dispute resolution. The comparative analysis underscores the need for Indonesia to develop a specific legal framework for ODR that integrates substantive procedures, technological infrastructure, and institutional capacity. This would enable efficient, cost-effective, and accessible legal remedies for consumers engaging in cross-border e-commerce. The study contributes to the ongoing discourse on consumer protection reform and recommends regulatory harmonization to ensure legal certainty, transparency, and justice in digital trade environments.